Comparing COVID-19 vaccine allocation strategies in India: A mathematical modelling study. (February 2021) - Foy, Brody H.; Wahl, Brian; Mehta, Kayur; Shet, Anita; Menon, Gautam I.; Britto, Carl
Highlights: We model the effectiveness of COVID vaccine strategies in India using a SEIR model. Regardless of efficacy, prioritized vaccination of >60 years olds leads to greater reductions in deaths than prioritized vaccination of other age groups. Prioritized vaccination of younger adults (20–40 years) often reduced symptomatic infections most significantly. Increased speed of rollout of COVID-19 vaccine reduced the relative differences between different vaccine allocation strategies. Vaccination along with non-pharmaceutical measures of disease control offers the best chance in curbing the duration of this outbreak. Abstract: Background: The development and widespread use of an effective SARS-CoV-2 vaccine could prevent substantial morbidity and mortality associated with COVID-19 and mitigate the secondary effects associated with non-pharmaceutical interventions. Methods: We used an age-structured, expanded SEIR model with social contact matrices to assess age-specific vaccine allocation strategies in India. We used state-specific age structures and disease transmission coefficients estimated from confirmed incident cases of COVID-19 between 1 July and 31 August 2020. Simulations were used to investigate the relative reduction in mortality and morbidity of vaccine allocation strategies based on prioritizing different age groups, and the interactions of these strategies with concurrent non-pharmaceutical interventions. Given the uncertainty associated with COVID-19 vaccine development, we varied vaccine characteristics in the modelling simulations. Results: Prioritizing COVID-19 vaccine allocation for older populations (i.e., >60 years) led to the greatest relative reduction in deaths, regardless of vaccine efficacy, control measures, rollout speed, or immunity dynamics. Preferential vaccination of this group often produced relatively higher total symptomatic infections and more pronounced estimates of peak incidence than other assessed strategies. Vaccine efficacy, immunity type, target coverage, and rollout speed significantly influenced overall strategy effectiveness, with the time taken to reach target coverage significantly affecting the relative mortality benefit comparative to no vaccination. Conclusions: Our findings support global recommendations to prioritize COVID-19 vaccine allocation for older age groups. Relative differences between allocation strategies were reduced as the speed of vaccine rollout was increased. Optimal vaccine allocation strategies will depend on vaccine characteristics, strength of concurrent non-pharmaceutical interventions, and region-specific goals.